Early Childhood Cumulative Risk and Temperament Predict Preadolescent Appraisal and Coping and Adolescent Psychopathology - Michele R. Smith; Caitlin Stavish; Autumn Eo; Ana Funes Gonzalez; Krystal H. Parrish; Stephanie Thompson; Katie A. McLaughlin; Liliana J. Lengua (Clinical Psychological Science, 2026)
In this study, we tested a model of early childhood adversity, temperament, and their interaction predicting appraisal (threat) and coping (active, avoidant) styles that increase risk for psychopathology ( N = 306). Temperament was assessed at 3 to 5.5 years, appraisal and coping styles were assessed at 11 to 12 years, and internalizing and externalizing problems were assessed at 11 to 12 years and 15 to 16 years. Threat was predicted by higher fear and Cumulative Risk × Frustration interaction, which also predicted avoidance. High-frustration children demonstrated more threat and avoidance at lower levels of cumulative risk than children experiencing greater risk and children low in frustration. An Effortful Control × Cumulative Risk interaction predicted coping. Higher cumulative risk was related to more active and avoidant coping for low-effortful control children. Threat and coping were concurrently associated with preadolescent psychopathology, which predicted higher adolescent psychopathology. Such longitudinal models are critical to articulate the processes of risk for psychopathology in temperamentally vulnerable children exposed to adversity.